DEVELOPMENT OF DIGITAL FLIPBOOK E-MODULES TO SUPPORT PROJECT-BASED LEARNING IN DESCRIPTIVE TEXT MATERIALS IN FIFTH GRADE ELEMENTARY SCHOOLS - Sari, Ayu Puspita; Arafah, Andi Asrafiani; Septika, Hety Diana; Makmun, Makmun; Hidayat, Taufik; Sukriadi, Sukriadi (JURNAL NALAR PENDIDIKAN, 2025)
This study aims to develop and assess the feasibility of a Project-Based Learning (PjBL)-based e-module using a flipbook for fifth-grade descriptive text material. The background of this research is students' low writing skills and the limited use of interactive teaching methods. The research employed the Research and Development (RnD) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study involved 28 fifth-grade students from SD Negeri 021 Sungai Kunjang. Data were collected through interviews, questionnaires, and observations, with feasibility assessments from experts and feedback from students and teachers. The results indicate that the developed e-module achieved a high feasibility rating: 96% from media experts, 95% from material experts, 97% from language experts, and 98% from teachers. Student responses were highly positive, categorized as "very practical" (87% in small-scale trials and 96% in large-scale trials). Teachers also rated it as "very practical," with a score of 97%. In conclusion, the e-module is suitable for use in learning. Future research is recommended to incorporate more visual elements, test its effectiveness in teaching, and expand the content variety.